Targeting of phosphorylated tau at threonine 181 by a Qβ virus‐like particle vaccine is safe, highly immunogenic, and reduces disease severity in mice and rhesus macaques - Maphis, Nicole M.; Hulse, Jonathan; Peabody, Julianne; Dadras, Somayeh; Whelpley, Madelin J; Kandath, Manas; Wilson, Colin; Hobson, Sasha; Thompson, Jeff; Poolsup, Suttinee; Beckman, Danielle; Ott, Sean P; et al. (Alzheimer's & dementia, 2025)
INTRODUCTION Pathological accumulation of tau (pTau) contributes to various tauopathies, including Alzheimer's disease (AD), and correlates with cognitive decline. A rapid surge in tau‐targeted approaches via anti‐sense oligonucleotides, active/passive immunotherapies suggests that targeting p‐Tau is a viable strategy against tauopathies. METHOD We describe a multi‐species validation of our previously described Qß virus‐like particle (VLP)–based vaccine technology targeting phosphorylated tau on threonine 181 (pT181‐Qß). RESULTS Two vaccine doses of pT181‐Qß, without any adjuvants, elicited robust antibody responses in two different mouse models of tauopathy (PS19 and hTau) and rhesus macaques. In mouse models, vaccination reduced AT180+ hyperphosphorylated, Sarkosyl insoluble, Gallyas silver positive tau, inflammasomes/neuroinflammation, and improved recognition memory and motor function without inducing adverse T‐cell activation. Anti‐pT181 antibodies are reactive to pTau in human AD brains, engage pT181+ tau in human brain lysates, and are central nervous system bioavailable. DISCUSSION Our results suggest the translational utility of pT181‐Qß against tauopathies. Highlights Icosahedral display of phosphorylated tau at threonine 181 (pT181) Qß virus‐like particle surface (“pT181‐Qß” vaccine) induces a robust immune response in mice and in non‐human primates (NHPs) pT181‐Qß vaccination reduces pathological tau (pTau) and brain atrophy, and improves memory and motor function in PS19 and hTau mice. pT181‐Qß vaccination–induced immunoglobulin Gs (IgGs) are safe, Th2 skewed (anti‐inflammatory), specific to pTau in human AD brain, and efficiently engage pT181 in NHPs and human brain lysate. pT181+ tau in human plasma correlates with the neurofilament light in subjects with mild cognitive impairment (MCI)—suggesting the presence of pT181‐Qß vaccine target in the early disease state.